Modifying mango trees for export - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A pilot project in Jamaica demonstrates how common (wild) mango trees can be rapidly modified to enable them to produce high value fruit for export. The technique, known as 'topworking', involves clearing the main trunk and girdling it at about 2 m...